2008
DOI: 10.1186/1471-2466-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Do airway metallic stents for benign lesions confer too costly a benefit?

Abstract: Background: The use of self-expanding metallic stents (SEMAS) in the treatment benign airway obstruction is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…USEMAS removal was uneventful, and there was no significant granulation tissue formation compared to higher rates reported in other studies [33,34]. This is due to the fact that stents were placed for a short time before neo-epithelialization occured.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…USEMAS removal was uneventful, and there was no significant granulation tissue formation compared to higher rates reported in other studies [33,34]. This is due to the fact that stents were placed for a short time before neo-epithelialization occured.…”
Section: Discussionmentioning
confidence: 39%
“…Another study by Chan et al [34] showed a higher long-term complication rate in patients who had metallic stent for benign airway disease, but 90% of stents were removed uneventfully. Thus, it is important to emphasize that when metallic stents are left for a prolonged period of time, they are harder to remove and are associated with increased complications [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…In a series of 40 patients this improvement was evident in stridor in 73% of cases, breathlessness in 71%, cough in 79% and in sputum clearance in 75% 91. In five series where a proportion of patients had lung function assessed before and after stent insertion,89 91–94 FEV 1 , forced vital capacity (FVC) and airway resistance (where measured) improved.…”
Section: Therapeutic Procedures For Malignant Disease: Malignant Airwmentioning
confidence: 96%
“…In De Gregorio et al study, three out of four steel stents that were used to treat benign lesions in the trachea had to be removed a year after their deployment 18 . We have corroborated these findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Steel stents were first used in the tracheobronchial tree with initially favorable results, but quickly revealed shortcomings 3,17,18 . In De Gregorio et al study, three out of four steel stents that were used to treat benign lesions in the trachea had to be removed a year after their deployment 18 .…”
Section: Discussionmentioning
confidence: 99%